Seroprevalence of Viral Infections in Domestic Cats in Costa Rica - Dolz, Gaby (2018)
A cross-sectional survey of a convenient sample of domestic cats from Costa Rica’s greater metropolitan area was carried out to determine the prevalence of antibodies against feline herpesvirus type 1 (FHV-1), feline parvovirus (FPV), feline immunodeficiency virus (FIV) and antigens of feline leukemia virus (FeLV). Blood samples were collected from at least 96 cats from June 1998 to December 2001; data related to the individual cats and household variables were obtained using a questionnaire. Antibodies against FHV-1 were found in 71.9% of the cats sampled, but only 25.0% of them had a history of previous vaccination. The prevalence of FPV was 92.8%, and all positive cats showed protective antibodies titres; however, only 16.5% of them were previously vaccinated. Antigens of FeLV were detected in 16.7% of the sampled cats; 11 (64.7%) of the 17 positive cats were older than 1 year at the time of testing. No differences were found between the percentage of seropositive males and females. Antibodies against FIV were detected in 8.8% of the samples tested; 8 (88.8%) of the seropositive cats were older than 1 year of age, and a greater proportion of seropositive males (66.6%) was found.